2008
DOI: 10.1016/j.canlet.2008.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 14-3-3σ expression in human thyroid carcinoma is epigenetically regulated by aberrant cytosine methylation

Abstract: Increased 14-3-3σ expression has been observed by immunohistochemistry in papillary and anaplastic tumors, but not follicular thyroid cancers. 14-3-3σ mRNA expression and methylation status was examined in tumor cell lines and primary thyroid tissues using real-time RT-PCR, bisulfite sequencing and methylation-specific PCR. Most of the 27 CpG's in the gene's CpG island were methylated in normal thyroid, TPC-1, NPA, FTC-238 and 2-7, which did not express 14-3-3σ. In contrast, they were unmethylated in KAK-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…In tumor cells LINE-1 repeats, satellite DNA, and moderately repeated DNA sequences become unmethylated, while genes containing CpG cluster become hypermethylated, rendering them transcriptionally silent (For review see [35]). Prime candidates for this type of repression are tumor suppressor genes such as p16 and 14-3-3 sigma [98-100]. Methylated CpGs also form mutation hot spots within coding regions of tumor suppressor genes like p53 [101, 102].…”
Section: The Epigenetic Switch In Cancermentioning
confidence: 99%
“…In tumor cells LINE-1 repeats, satellite DNA, and moderately repeated DNA sequences become unmethylated, while genes containing CpG cluster become hypermethylated, rendering them transcriptionally silent (For review see [35]). Prime candidates for this type of repression are tumor suppressor genes such as p16 and 14-3-3 sigma [98-100]. Methylated CpGs also form mutation hot spots within coding regions of tumor suppressor genes like p53 [101, 102].…”
Section: The Epigenetic Switch In Cancermentioning
confidence: 99%
“…Epigenetic dysfunction is another of the common hallmarks of malignancy, as an ever-growing list of epigenetically altered genes in cancer attests to. Our laboratory alone has definitively demonstrated the importance of epigenetic regulation of multiple genes in cancer, including maspin (63,85), desmocollin 3 (228), 14-3-3 sigma (162), and the critical mitochondrial antioxidant enzyme manganese superoxide dismutase (121). Multiple analyses have demonstrated that global epigenetic dysregulation is a ubiquitous finding in essentially all assayed tumors, and there is mounting evidence that epigenetic changes may even precede malignant transformation during carcinogenesis (73).…”
mentioning
confidence: 99%
“…In addition, it has been postulated that this molecule that expresses under direct activation of p53, is induced after DNA damaging and plays a significant roles during several kind of malignancies including breast, prostate, skin and colon cancers (LODYGIN and HERMEKING 2005). Epigenetic analysis suggested that 14-3-3σ expression in thyroid cancer cell lines is epigenetically controlled by an alteration in CpG methylation (Lal et al 2008). More studies are required to elucidate its function in thyroid malignancies.…”
Section: The 14-3-3σmentioning
confidence: 97%
“…14-3-3σ also named human mammary epithelium-specific marker 1 (HME1), is a cell cycle regulator which acts as a G2/M arresting molecule expressing in malignant thyroid tissues (Lal et al 2008). Interestingly, 14-3-3σ observed to be expressed in all papillary carcinomas but not follicular carcinomas and adenomas, and it proposed that this protein might not be required for development of thyroid follicular tumors (Ito et al 2003).…”
Section: The 14-3-3σmentioning
confidence: 97%